Adapting the organization of a company's accounting policy to include environmental aspects - Sadowska, Beata; Ankudo-Jankowska, Anna; Starosta-Grala, Monika (Środowiskowa organizacja rachunkowości, 2019)
Business entities are obliged to keep accounting records in accordance with specific and internally adopted accounting principles (policy) whose basic element is a chart of accounts. Entities are obliged to follow the adopted accounting principles in a reliable and transparent way and to present a financial situation, a financial result and the non-financial aspects of business activities.. The purpose of the article is to define the essence of the organization of accounting principle (policy) in a business entity and to describe desirable changes in the accounting policy and a chart of accounts as a condition for adapting a business entity to including environmental aspects. Apart from the introduction and the conclusion, the article includes three elements focusing on such issues as: accounting as a generator of information on environmental protection, a theoretical analysis of the organization of accounting principles (policy), and a model perspective of environmental accounting principles (policy) and a sample chart of accounts
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 215-229
Keywords: natural environment; organization of accounting; accounting; chart of accounts; accounting principles; środowisko przyrodnicze; organizacja rachunkowości; rachunkowość; plan kont; zasady rachunkowości